The Neo-Assyrian shield: evolution, heraldry, and associated tactics - De Backer, Fabrice (Lockwood Press, 2016)
This handbook analyses the different types of shields used by soldiers in the Neo-Assyrian army and their opponents. Written, visual, and material sources are analysed to illustrate practical aspects of defensive weaponry in the ancient Near East in the first millennium B.C. The origins, use, evolution, and manufacture of shields are considered in presenting a typology of these objects. The first study of its kind, this work will appeal to advanced scholars, graduate students, general non-specialists, and re-enactors alike